Do Changes in Language Context Affect Visual Memory in Bilinguals? - Schroeder, Scott R. (Frontiers in Human Neuroscience, 2019)
Language is often present when people are encoding visual memories. For bilinguals, this language context can have different forms (i.e., Language A, Language B, or both Language A and B), and can change over the course of events. The current study examined whether a change in language context during a visual event or between visual events affects a bilingual’s ability to remember visual information. English-Spanish bilinguals and control participants encoded three lists of novel shapes amid different task-irrelevant language contexts. Following each list, participants completed a free recall test in which they drew the novel shapes they remembered. Results indicated that a change in language context between events, but not during events, affected visual memory. Specifically, the switch in language context between the second and third event (such as an English context in list 2 switching to a Spanish context in list 3) produced a reliable memory advantage for the English-Spanish bilinguals (relative to the control participants). The results offer preliminary evidence that task-irrelevant language context can influence a bilingual’s ability to remember non-linguistic information, as well as further evidence for context effects and multi-sensory effects in memory